2019
DOI: 10.1105/tpc.18.00723
|View full text |Cite
|
Sign up to set email alerts
|

The bZIP1 Transcription Factor Regulates Lipid Remodeling and Contributes to ER Stress Management in Chlamydomonas reinhardtii

Abstract: Youngsook Lee, ylee@postech.ac.kr. 24 25The authors declare there is no conflict of interests. 26 27Running title: CrbZIP1 modulates membrane lipids under ER stress 28 29One-Sentence Summary: The mRNA of a Chlamydomonas bZIP transcription factor is 30 spliced by CrIRE1 under ER stress, and the resulting protein protects Chlamydomonas cells 31 from ER stress by modulating lipid remodeling. 32 33 34Keywords: bZIP; Chlamydomonas; DGTS; ER stress; pinolenic acid 35 36Word count: 7958 words 37 38 39 2 ABSTRACT 40En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 44 publications
0
33
1
Order By: Relevance
“…Since over-dominant genes of both reciprocal crosses were enriched in these three important pathways, we further analyzed the over-dominant genes of the reciprocal crosses and found seven shared over-dominant genes. Among these, HMGCL [41] and four novel genes annotated in the carboxylesterase family [42,43], FOXP coiled-coil domain [44,45], bZIP transcription factor [46,47,48], and reverse transcriptase [49], respectively, were reported to be associated with lipid metabolism. Interestingly, HMGCL was a shared over-dominant gene in the reciprocal crosses, which was annotated by KEGG pathways of butanoate metabolism, synthesis and degradation of ketone bodies, and valine, leucine, and isoleucine degradation, indicating that HMGCL plays important roles in heterosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since over-dominant genes of both reciprocal crosses were enriched in these three important pathways, we further analyzed the over-dominant genes of the reciprocal crosses and found seven shared over-dominant genes. Among these, HMGCL [41] and four novel genes annotated in the carboxylesterase family [42,43], FOXP coiled-coil domain [44,45], bZIP transcription factor [46,47,48], and reverse transcriptase [49], respectively, were reported to be associated with lipid metabolism. Interestingly, HMGCL was a shared over-dominant gene in the reciprocal crosses, which was annotated by KEGG pathways of butanoate metabolism, synthesis and degradation of ketone bodies, and valine, leucine, and isoleucine degradation, indicating that HMGCL plays important roles in heterosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yamaoka et al (2019) have found that the TF basic leucine zipper 1 (BZIP1) from C. reinhardtii (CrBZIP1) is involved in ER stress response. The protein promotes expression of genes involved in the unfolded protein response.…”
Section: Transcription Factorsmentioning
confidence: 99%
“…As another example, Yamaoka et al identified a bZIP transcription factor involved in the ER stress response through lipid remodeling in Chlamydomonas [ 65 ].…”
Section: Tf-based Metabolic Engineering In Microalgaementioning
confidence: 99%